Determining Methyl-Esterification Patterns in Plant-Derived Homogalacturonan Pectins - Yu, Yang; Cui, Liangnan; Liu, Xianbin; Wang, Yuwen; Song, Chenchen; Pak, UnHak; Mayo, Kevin H.; Sun, Lin; Zhou, Yifa (Frontiers in Nutrition, 2022)
Homogalacturonan (HG)-type pectins are nutrient components in plants and are widely used in the food industry. The methyl-esterification pattern is a crucial structural parameter used to assess HG pectins in terms of their nutraceutical activity. To better understand the methyl-esterification pattern of natural HG pectins from different plants, we purified twenty HG pectin-rich fractions from twelve plants and classified them by their monosaccharide composition, FT-IR signatures and NMR analysis. FT-IR shows that these HG pectins are all minimally esterified, with the degree of methyl-esterification (DM) being 5% to 40%. To examine their methyl-esterification pattern by enzymatic fingerprinting, we hydrolyzed the HG pectins by using endo-polygalacturonase. Hydrolyzed oligomers were derivatized with 2-aminobenzamide and subjected to liquid chromatography-fluorescence-tandem mass spectrometry (HILIC-FLR-MSn). Twenty-one types of mono/oligo-galacturonides having DP values of 1 to 10 were found to contain non-esterified monomers, dimers and trimers, as well as oligomers with 1 to 6 methyl-ester groups. In these oligogalacturonides, MSn analysis demonstrated that the number of methyl-ester groups in continuous sequence was 2 to 5. Mono- and di-esterified oligomers had higher percentages in total methyl-esterified groups, suggesting that these is a random methyl-esterification pattern in these HG pectins. Our study analyzes the characteristics of the methyl-esterification pattern in naturally occurring plant-derived HG pectins, findings that will be useful for further studying HG structure-function relationships.